Chinese business networks state, economy and culture - Chan, Kwok Bun (Prentice Hall, Pearson Education Asia Pte. Ltd. ; Nordic Institute of Asian Studies, 2000)
Using the proflierating volume of social science data and concepts on the subject, this book attempts to provide an alternative interpretation of the business conduct of the ethnic Chinese of East and Southeast Asia.